Peran Lipid Nanoparticles dalam Teknologi Vaksin mRNA: Peluang dan Hambatan - feliadewi ruth (Jurnal Farmasi Ma Chung: Sains, Teknologi, dan Klinis Komunitas, 2025)
Lipid nanoparticles (LNP) constitute critical delivery systems for both vaccine formulations and mRNA-based therapeutic strategies; nevertheless, concerns regarding their efficacy, safety, and design optimization continue to be prevalent. This review is designed to systematically evaluate the function of LNP within the framework of mRNA vaccine technologies, emphasizing mechanistic insights, stability assessments, safety considerations, and challenges in manufacturing. Comprehensive literature reviews were conducted utilizing databases such as PubMed, ScienceDirect, and Semantic Scholar for peer-reviewed articles published between the years 2020 and 2025, with the application of relevant keywords. From the 418 articles identified, 57 met the inclusion criteria following rigorous screening and were subjected to thematic analysis based on parameters including efficacy, safety, stability, and optimization strategies. The results reveal that LNP substantially enhances mRNA stability and expression in vivo, fortifies robust immune responses, and serves a vital role in the effective deployment of various mRNA vaccines, particularly those aimed at combating infectious diseases. However, challenges such as sensitive stability, insufficient endosomal escape, hepatic accumulation, toxicity concerns, and complex manufacturing processes remain significant issues of concern. It is concluded that while current formulations of LNP exhibit effectiveness for specific applications, they are not universally optimal; consequently, further advancements in design, targeting, and production methodologies are imperative to improving the efficacy, safety, and accessibility of LNP-based mRNA vaccines.